Strangers in a Strange Land: The Identity of Galatian Rulers in Thrace and Anatolia at the Turn of the 3rd to the 2nd century BC - Julian Gieseke (Imafronte, 2024)
The Gallic invasion of Greece in 280/279 BC left a deep mark in the collective memory of the Greeks. From then on, they represented the Celts as the stereotypical ‘barbarians’ – primitive, wild, violent and without any culture of their own. As the newcomers had established permanent kingdoms in Thrace and Phrygia, however, both sides had to learn how to deal with each other. The paper asks how the rulers of the Galatians on both sides of the Bosporus handled this challenge and how this influenced their own identity. To go beyond existing research, the analysis draws both on the literary Greek sources and the coinage which the Eastern Celts started to produce in the 3rd century BC. It will be shown that the Galatian elites quickly adapted to the political practices of the Hellenistic world and confidently asserted their own place within it, mixing their own customs with Greek and local (Thracian, Anatolian) elements to create a unique blend of identity.